Parent goals : the millennial's guide to new parent preparedness - Garrett, Lindsay C. M. (Wonderwell, 2021)
"Child welfare and adoption specialist Lindsay Garrett, LCSW, teaches millennials considering having kids how to emotionally prepare for parenthood, determine their parenting style and values, and establish sustainable support"--